2022
DOI: 10.1007/s44155-022-00021-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating change across time in prevalence or association: the challenges of cross-study comparative research and possible solutions

Abstract: Cross-study research initiatives to understand change across time are an increasingly prominent component of social and health sciences, yet they present considerable practical, analytical and conceptual challenges. First, we discuss the key challenges to comparative research as a basis for detecting societal change, as well as possible solutions. We focus on studies which investigate changes across time in outcome occurrence or the magnitude and/or direction of associations. We discuss the use and importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Details for specific studies selected can be found in Supplementary Study quality was assessed using a modified version of the Newcastle-Ottawa Scale (NOS: [27]; see also [28,29]). Modifications to the quality assessment were to ensure quality assessment was aligned to cohort comparison study design (see [30]) and also to time trends research. In particular, comparability of study cohorts and measures were included as key domains in our quality assessment (Supplementary Table 3).…”
Section: Literature Search Strategy and Quality Assessmentmentioning
confidence: 99%
“…Details for specific studies selected can be found in Supplementary Study quality was assessed using a modified version of the Newcastle-Ottawa Scale (NOS: [27]; see also [28,29]). Modifications to the quality assessment were to ensure quality assessment was aligned to cohort comparison study design (see [30]) and also to time trends research. In particular, comparability of study cohorts and measures were included as key domains in our quality assessment (Supplementary Table 3).…”
Section: Literature Search Strategy and Quality Assessmentmentioning
confidence: 99%
“…Comparisons between the cohorts should be made cautiously because of differences in question scope and wording. We identified some of the challenges of cross-study comparisons and suggested methods for dealing with these based on published guidance [40]. For example, we established percentage cost differences between groups and genders to facilitate intercohort comparisons.…”
Section: Strengths and Limitationsmentioning
confidence: 99%